Meniscus-assisted solution printing of large-grained perovskite films for high-efficiency solar cells - Ming He (Nature Portfolio, 2017)
The morphology control of metal halide perovskite crystalline films is of importance to enable high-performance solar cells. Here, Heet al. use a meniscus-assisted solution-based method to print microsized perovskite grains at 60 °C, which results in high optoelectronic device efficiency of 20%.